2010
DOI: 10.1039/c0mb00069h
|View full text |Cite
|
Sign up to set email alerts
|

Metabolically incorporated photocrosslinking sialic acid covalently captures a ganglioside–protein complex

Abstract: When photoirradiated, an unnatural sialic acid analog can covalently capture the complex formed by ganglioside GM1 and cholera toxin subunit B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 25 publications
1
56
0
1
Order By: Relevance
“…NEU3 activity on cells may be a result of incorporation of SiaDAz(2me) into ganglioside substrates. 33,34 Interestingly, we found that NanA, AUNA, and NEU4, each of which showed no detectable activity toward SiaDAz(2me) in our cell-free assay, cleaved between 50 and 70 % of SiaDAz(2me) on cells surfaces. Of all the sialidases tested, only STNA was completely inactive toward SiaDAz(2me) on BJAB K20 cell surfaces, with 100 % of SiaDAz(2me) remaining after STNA treatment.…”
Section: Resultsmentioning
confidence: 69%
“…NEU3 activity on cells may be a result of incorporation of SiaDAz(2me) into ganglioside substrates. 33,34 Interestingly, we found that NanA, AUNA, and NEU4, each of which showed no detectable activity toward SiaDAz(2me) in our cell-free assay, cleaved between 50 and 70 % of SiaDAz(2me) on cells surfaces. Of all the sialidases tested, only STNA was completely inactive toward SiaDAz(2me) on BJAB K20 cell surfaces, with 100 % of SiaDAz(2me) remaining after STNA treatment.…”
Section: Resultsmentioning
confidence: 69%
“…Lysates incubated with UDP-GlcNDAz produced a product whose mass corresponded to the intact O-GlcNDAz-modified peptide (m∕z ¼ 1; 309) and an additional product whose mass was consistent with loss of N 2 from the O-GlcNDAz-modified peptide (m∕z ¼ 1; 281). Loss of N 2 likely occurs during the mass spectrometry ionization step, a phenomenon we have observed with other diazirine-containing molecules (19). When OGTcontaining lysates were incubated with an equimolar mixture of UDP-GlcNAc and UDP-GlcNDAz, masses corresponding to both O-GlcNAc-and O-GlcNDAz-modified peptides were observed.…”
Section: Resultsmentioning
confidence: 94%
“…[8, 19, 21, 27] However, attempts to produce SiaDAz-containing glycoconjugates in other cell lines resulted in variable outcomes. To assess the cell line-dependence of SiaDAz incorporation, we cultured fifteen cell lines with 100 μM Ac 4 ManNDAz for 48–72 h. We isolated the membrane fractions from these cells, released the glycoconjugate-bound sialic acids, and quantified the amounts of Neu5Ac and SiaDAz.…”
Section: Resultsmentioning
confidence: 99%